Mixing Rules of Dielectric Properties of Aqueous Organic Solution - Zhu Jia, Guo; Qing Yang, Xiao; Ma Huang, Ka (Asian Journal of Chemistry, 2011)
Many dielectric properties of aqueous organic solution over the microwave frequency have been investigated, their frequency-dependent dielectric properties can be summarized by three parameters in the Debye equation i.e., a static dielectric constant, a high-frequency limiting dielectric constant and a dielectric relaxation time constant. On the basis of electrostatics, rate theory, solution thermodynamics and hydrogen bond dynamics we have summarized dielectric "mixing rules" that describe the frequency-dependent dielectric properties of the solvent organic aqueous solution based on solution composition and the dielectric parameters for the solution components. These "mixing rules" yield good agreement between the predicted and experimental dielectric properties of DMF-water mixtures over all solution compositions.